Mathematical modelling of improving the physical and mechanical properties of vehicle movement parameters in mountain conditions - Mamadaliev Foziljon Abdellevich; Babaeva Zinnat Rizakulovna (Peerian Journals Publishing, 2024)
The article discusses new scientific approaches to the laws of vehicle movement on a mountain road and their analysis in a new interpretation. The results of scientific research related to improving traffic safety in extreme road conditions are presented. Scientific proposals are given
Keywords: motion; motion parameters; mountain conditions